2018
DOI: 10.14260/jemds/2018/930
|View full text |Cite
|
Sign up to set email alerts
|

Is RHTMD a New Predictor for Assessment of Difficult Intubation in Non-Obese Patients?

Abstract: BACKGROUND The recognition of difficult intubation during pre-operative check-up is very important for the anaesthesiologist. Various anatomical parameters assist in predicting difficult intubation. Till date, there are no predictors available to precisely assess the risk of difficult intubation, pre-operatively.Therefore, we aim to identify the adequacy of predictors for preoperative assessment of difficult intubation. MATERIALS AND METHODSAfter ethical approval of Institutional Ethics Committee, a total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Observational studies reported comparative findings for facial and jaw features and anatomical measurement for difficult versus nondifficult airway patients as well as sensitivity, specificity, positive predictive, negative predictive, and accuracy values for difficult laryngoscopy and intubation. Findings for facial and jaw features, 7–11,13,14,18,27,33,38–40,42,43,45–47,49,51–54,57,58,64,68,123–159 anatomical measurements, 7–11,13–15,18,22,23,27–30,33,35,37–40,45–47,49,51–54,57,58,60, 64,65,68,70,123–132,134–154,156,158–203 and ultrasound anatomical measurements 69,139,162,170,194,196,203–213 were shown to have very high predictive and comparative variability, with sensitivity, specificity, and significance values ranging from low to very high across all patient measures (Category B2-E evidence). No single characteristic was identified as consistently being more predictive than another, and multivariate measures intended to predict difficult airways were too few and diverse among the studies to determine a common set of predictors.…”
Section: Guidelinesmentioning
confidence: 99%
“…Observational studies reported comparative findings for facial and jaw features and anatomical measurement for difficult versus nondifficult airway patients as well as sensitivity, specificity, positive predictive, negative predictive, and accuracy values for difficult laryngoscopy and intubation. Findings for facial and jaw features, 7–11,13,14,18,27,33,38–40,42,43,45–47,49,51–54,57,58,64,68,123–159 anatomical measurements, 7–11,13–15,18,22,23,27–30,33,35,37–40,45–47,49,51–54,57,58,60, 64,65,68,70,123–132,134–154,156,158–203 and ultrasound anatomical measurements 69,139,162,170,194,196,203–213 were shown to have very high predictive and comparative variability, with sensitivity, specificity, and significance values ranging from low to very high across all patient measures (Category B2-E evidence). No single characteristic was identified as consistently being more predictive than another, and multivariate measures intended to predict difficult airways were too few and diverse among the studies to determine a common set of predictors.…”
Section: Guidelinesmentioning
confidence: 99%
“…Numerous airway assessment methods are in practice like Wilson risk score, head and neck movement, mouth opening or inter-incisor gap, thyromental distance, horizontal length of mandible, sternomental distance and mallampati test but sensitivities ranges upto 33% 7 . Few studies are available on combination of these methods to assess the predictive values like upper lip bite and thyromental distance [8][9][10] . This study aims to evaluate validation of MMT by adding SMD and TMD in prediction of difficult intubation or laryngoscopy in surgical patients.…”
Section: Introductionmentioning
confidence: 99%